1985
DOI: 10.1007/bf00422959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of coupling the breathing- and cycling rhythms on oxygen uptake during bicycle ergometry

Abstract: The influence of the degree of coupling between the breathing and cycling rhythms (K) on oxygen uptake (Vo2) was examined in 30 volunteers. They cycled on an ergometer with a load equal to 50% of their work capacity 170 in two experimental runs with spontaneous breathing rhythm, and in a further two runs with acoustically triggered breathing. K was continuously ascertained. Vo2 and other respiratory parameters were measured by an automatic "breath-by-breath analysis" system. In 16 subjects, Vo2-differences bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2

Year Published

1993
1993
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 14 publications
4
60
2
Order By: Relevance
“…Therefore, it is difficult to compare quantitatively the results of all relevant studies. However, the results of the present study and of our previous studies (Kohl et al 1981;Garlando et al 1985) are at least partially comparable, as in all of them we concentrated on the so called relative co-ordination (von Holst, 1939), characterized by significant relationships between the individual phases of both rhythms.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Therefore, it is difficult to compare quantitatively the results of all relevant studies. However, the results of the present study and of our previous studies (Kohl et al 1981;Garlando et al 1985) are at least partially comparable, as in all of them we concentrated on the so called relative co-ordination (von Holst, 1939), characterized by significant relationships between the individual phases of both rhythms.…”
Section: Discussionsupporting
confidence: 76%
“…The variety of the results may be explained by differences in experimental design, in the type of exercise and other experimental conditions and methods of evaluation which in turn make a quantitative comparison between the different studies more difficult. In two of our previous studies we found in the majority of the subjects a degree of co-ordination between limb movements and respiration during cycling (Kohl, Koller & Jiiger, 1981;Garlando, Kohl, Koller & Pietsch, 1985). Moreover, we found a higher degree of co-ordination in experienced rather than unexperienced cyclists.…”
Section: Introductionsupporting
confidence: 63%
“…Untrained bicyclists have been shown to maintain a 2:1, 3:1,4:1, 6:1, 3:2, and 5:2 ratio of pedal to respiratory frequency (Garlando, Kohl, Koller, & Pietsch, 1985;Paterson. Wood, Morton, & Henstridge, 1986).…”
Section: When Is Lrc Observed?mentioning
confidence: 99%
“…Consistent observations that energy expenditure (oxygen consumption) is lower during episodes of entrainment than nonentrainment (Garlando et al 1985;Bernasconi and Kohl 1993;Bonsignore et al 1998) suggest that LRC is a function of aerobic demands. Early investigations of LCR, however, were concerned primarily with identifying its eventual mechanical causes.…”
Section: Dynamicsmentioning
confidence: 78%